Investigating the cecal microbiota in broiler poultry farms and its potential relationships with animal welfare. (May 2022) - Di Marcantonio, Lisa; Marotta, Francesca; Vulpiani, Michele Podaliri; Sonntag, Quixi; Iannetti, Luigi; Janowicz, Anna; Serafino, Gabriella Di; Di Giannatale, Elisabetta; Garofolo, Giuliano
Abstract: The present study assessed the modulation of cecal microbiota and correlations with Campylobacter colonization and animal welfare status. For these purposes, we conducted a cross sectional study of the cecal microbiota from 187 broilers reared in 13 batches from 10 poultry farms by performing 16S rRNA sequencing (regions V3–4). The welfare of each batch was assessed using a simplified Welfare Quality® protocol, scoring higher in organic batches, compared to both antibiotic-free and conventional batches. The bioinformatics analyses were conducted in QIIME 2 and a linear discriminant analysis determined the association between microbiota and animals with different Campylobacter carriage status and welfare levels. In the microbiota from the subjects negative for Campylobacter or with high welfare scores, Bacteroidetes was the predominant phylum with the genus Megamonas significantly increased in abundance. A greater abundance of Parabacteroides, Phascolarctobacterium, Helicobacter in poultry negative for Campylobacter was also found at the genus level. Animals with the lowest welfare scores showed an increased abundance of Proteobacteria . The results suggested a different microbial composition and diversity in the analyzed groups. Highlights: The richness of the cecal microbiota may help the broiler chickens contain Campylobacter colonization. Interactions between the broiler gut microbiota, the animal welfare and the presence or absence of Campylobacter. Animal welfare standards like housing, health and food in animal production may be linked with cecal microbiota composition.